HUBUNGAN PENGETAHUAN SANTRI TENTANG PENCEGAHAN SKABIES DENGAN KEJADIAN SKABIES DI PANTI ASUHAN DARUSSALAM PALEMBANG: Dea Mega Arini, Sri Mulia Sari, Fitri Rizkiah (JURNAL SMART ANKes, 2021)
Scabies is a disease which very itchy, especially at night before bed, contagious, and is caused by sarcoptes scabiei. Based on WHO, Objective : scabies can affect more than 130 million people at any time. The aim of this study was to determine the relationship of student knowledge Prevention and Scabies Case at Orphanage Darussalam. Method : The method of this study is descriptive analytic trough cross sectional approach. The population in this study were all student at Orphanage Darussalam. The sample was 264 respondent. The technique of sampling using stratified random sampling. Result : The result of this study found that respondent who has good knowledge has 120 respondents (82.8%) were not scabies, while respondents who have enough knowledge was 47 respondents (39.5%) were not scabies. Based on the statistical test Chi-square found that p value (0.000) < value a (0.05), its means there is a significant relationship of Student Knowledge Prevention and Scabies Case at Orphanage Darussalam. For orphanages, it is expected that they can conduct health education and seminars for orphans about health, especially related to personal hygiene and education about scabies every 1-3 months.